The burden, risk factors, and antimicrobial susceptibility pattern associated with extended-spectrum beta-lactamase-producing E. coli and K. pneumoniae carriage among neonates and their surroundings at a referral hospital in the Moshi municipality - Mshana, Happyness J.; Kovacs, Dorottya; Muro, Florida; Zadoks, Ruth; Oravcova, Katarina; Matthews, Louise; Mmbaga, Blandina T. (Frontiers in Antibiotics, 2025)
IntroductionInfections are a major driver of broad-spectrum antibiotic use. This wide use of antibiotics contributes to the emergence of antimicrobial resistance globally that poses a threat to human and animal health. Infections continue to be a major cause of death among pregnant women and neonates. Therefore, this study aimed to assess the burden of extended-spectrum beta-lactamase (ESBL)-producing E. coli and K. pneumoniae carriage among neonates and their surroundings admitted to a referral hospital in Northeast Tanzania.MethodologyThe burden of ESBL-producing E. coli and K. pneumoniae in a neonatal ward was assessed by screening neonates’ rectums, maternal and healthcare workers’ hands, and neonatal cots. Isolates were cultured, identified, and tested for antimicrobial resistance, while generalized linear models identified risk factors for carriage.ResultsA total of 437 neonates were screened for ESBL-producing E. coli and K. pneumoniae, with 235 (54%) being male. In addition, 77 maternal hand swabs, 118 neonatal cots, and 45 healthcare workers’ hand swabs were collected. ESBL-producing K. pneumoniae was isolated from 198 neonates (45%), and E. coli from 96 (23%). Additionally, 5% of maternal hands and 22% of neonatal cots were contaminated with these resistant bacteria. Overall ampicillin resistance was frequent in ESBL-producing E. coli and ESBL K. pneumoniae neonatal colonization (n=261,100%), as was resistance to trimethoprim-sulfamethoxazole (n = 233,89%), gentamicin (n = 169, 66%), and tetracycline (n = 140,54%). Only three (1%) of the ESBL-producing E. coli and ESBL K. pneumoniae isolates were resistant to meropenem. Risk factors significantly associated with carriage of either ESBL-producing E. coli or K. pneumoniae were being born in an admission room [odds ratio (OR)=1.95, confidence interval (CI)=1.31-3.13, p=0.006] and delivery mode, with vaginal delivery associated with a reduced risk of carriage (OR=0.57, CI=0.35–0.92, p=0.023).ConclusionThe study reveals a high burden of ESBL-producing K. pneumoniae and E. coli in neonates and their environment, with frequent resistance to ampicillin and gentamicin. Hospital admission and cesarean delivery increase the risk of carriage, while vaginal delivery lowers it. Active screening upon admission and advanced diagnostic methods can help reduce transmission and guide effective antimicrobial treatment.